PERENCANAAN DAN PERANCANGAN AERATOR TAMBAK TENAGA ANGIN TIPE SAVONIUS DUA TINGKAT - Ahmad Farid; Irfan Santosa; Hadi Wibowo (JURNAL ILMIAH ULTRAS BREBES, 2017)
The purpose of the two-level type wind aerator planning aerator is the solution of several problems such as decreasing the quality of water; Aerator mill sold in the market price is relatively expensive and the previous aerator design with horizontal axle model that felt less maximal in obtaining wind energy from all directions. The method used in this research is the calculation by using the equations and experimental methods by testing on the design results. The results obtained from the calculation analysis that the aerator planning obtained data that the dimensions of the turbine (rotor radius) must be greater than the radius of the aerator wheel with a ratio of 1: 1.25 to 1: 4.15 where the power required between 0.013 HP to 0.213 HP. While the dimensions of wind turbine that is made is with radius 0.40 m and the radius of water wheel 0.15m. The test results that the vertical axis wind turbine with a diameter of 0.4 m at wind speeds of 3.7 to 5.53 m / s obtained a maximum turbine power of 14.3W, while in the application of increasing the amount of oxygen obtained the amount of dissolved oxygen in water 6,575 Mg / L. The comparison of the three aerators in terms of purchase price economy and operational costs where for the aerator of wind farms is obtained Rp. 157.00 / hour; Diesel power aerator Rp. 7107.00 / hour and electric power aerator is Rp. 2.048,00 / hour, wind power aerator still cheaper cost /hour Rp 1.891,00 to Rp. 6.950.00.